Feasibility, Design, and Deployment Requirements of TCR for Bistatic SAR Radiometric Calibration - Qiaona Zheng; Yu Wang; Jun Hong; Aichun Wang (Remote Sensing, 2018)
The trihedral corner reflector (TCR) is widely used as the calibration device in monostatic synthetic aperture radar (SAR) calibration, and the performance of the TCR in radiometric calibration has been studied and verified in depth. As for the bistatic SAR system calibration problem, there have been few published studies. There is a lack of knowledge regarding the exact bistatic radar cross-section (RCS) pattern of TCR with different bistatic angles, and it is also not clear whether the TCR can be used as the calibration target in bistatic SAR. Moreover, the bistatic and monostatic radar cross-section (RCS) characteristics of the TCR are different, even if the bistatic angle is very small. Therefore, the feasibility, design, and deployment requirements of the TCR for bistatic SAR calibration should be carefully investigated. In this paper, we outline the theoretical and practical requirements that need to be satisfied when choosing appropriate calibration devices for bistatic radiometric calibration. Based on these requirements, we analyzed the bistatic RCS patterns using electromagnetic simulation, and concluded that the TCR is feasible for bistatic SAR calibration under relatively small bistatic angles (less than 6°). The change of TCR boresight with the bistatic angle is not considered generally. However, we found that the TCR boresight and peak RCS will change with the bistatic angle. We have also proposed that the bistatic angle can be extended to 20° by taking the change of the TCR boresight into account. In this condition, we should get the TCR boresight according to the bistatic angle and then align it during the deployment. Both of these two conditions have their own unique advantages. Different error sources of TCR RCS from manufacture, misalignment, and deformation were investigated quantitatively with simulations, which can provide a theoretical basis for how to design a suitable TCR and guarantee the calibration accuracy for bistatic calibration. In addition, simulation results are different from those of monostatic calibration. Through experiments, we have further verified the feasibility by comparing the quality of bistatic SAR images and point target energy with several typical bistatic angles as the TCR boresight is considered or not. If the bistatic angle is larger than 6°, taking the TCR optimum boresight into account can improve imaging quality and point target energy.